P59 Changes in the body mass index and waist circumference distribution of adults aged 25–64 years in England, Scotland, and the United States, 1998–2012. (13th September 2016) - Scholes, S; Moody, A; Alfaro, T; Frenz, P; Dominguez, A; Sanchez-Romero, L; Vecino-Ortiz, A; Borges, C; Margozzini, P; Mindell, J; Cabrera, S; Barquera, S; et al.
Abstract : Background: Body Mass Index (BMI) and waist circumference (WC) are anthropometric indicators strongly associated with diabetes, cardiovascular disease, cancer and mortality. Focusing on secular changes in the mean values of BMI and WC can mask differences at the lower- and upper-tails of the distribution. Our network of health examination survey researchers from the Americas and the UK quantified secular changes in the BMI and WC distributions in England, Scotland, and the United States (US). Methods: Nationally-representative surveys of adults aged 25–64 y from similar time periods: Health Survey for England (1999–2012; n = 75, 813); Scottish Health Survey (1998–2011; n = 33, 010) and US National Health and Nutrition Examination Survey (1999–2012; n = 22, 340). Comparisons across time for mean values of measured height, weight, BMI, and WC and prevalence of obesity (BMI ≥ 30 kg/m 2 ) and abdominal obesity (WC ≥ 88 cm) were performed by age-standardising descriptive estimates by the direct-method to the 2000 US population. Quantile regression was used to evaluate whether BMI and WC values increased across survey years at pre-specified centiles of the distribution (5 th, 50 th, 95 th ). Models were adjusted for age, age-squared and survey year. Results: Mean BMI values for men (women) at baseline were 27.1 kg/m 2 (26.6 kg/m 2 ) in England; 27.1 kg/m 2 (26.8 kg/m 2 ) in Scotland; and 27.8 kg/m 2 (28.6 kg/m 2 ) in the US. Obesity and abdominal obesity increased for both sexes in England and in Scotland. In the US, obesity increased only for men; abdominal obesity increased only for women. Mean BMI increased by 0.4 kg/m 2 (0.7 kg/m 2 ) for men (women) in England; 0.8 kg/m 2 for both sexes in Scotland; and 1.0 kg/m 2 for men in the US. BMI at the 5 th centile was unchanged in England, but increased in Scotland and the US. Increases at the median and upper-tail occurred in each country: the increase at the 95 th BMI percentile was 2.1 kg/m 2 (1.3 kg/m 2 ) for men (women) in England; 1.9 kg/m 2 for both sexes in Scotland; and 2.0 kg/m 2 (1.9 kg/m 2 ) in the US (each P < 0.001). Mean WC increased by 2.1 cm (4.7 cm) for men (women) in England; 3.4 cm (6.5 cm) in Scotland; and 2.4 cm (3.8 cm) in the US. The increase at the 95 th WC percentile was 6.3 cm (5.4 cm) for men (women) in England; 3.6 cm (8.4 cm) in Scotland; and 4.5 cm (18.3 cm) in the US (each P < 0.001). Ongoing analyses will incorporate data from Chile, Colombia, Mexico, and Brazil. Conclusion: Secular increases in BMI and WC were fairly consistent by country for both sexes, with clear evidence of increases across the whole distribution in Scotland and the US.